Web-based Teacher Performance Appraisal Information System for Generasi Bintang School (Genbi) - Mendrofa, Lilis Karlina; Manalu, Mamed Rofendi (SEAN Institute, 2022)
Generasi Bintang School (Genbi) is one of the schools that implements teacher performance assessment to ensure a quality learning process for all students and to determine teacher promotion. The obstacle is that this assessment process is very complicated, if done manually, it takes a long time and is prone to errors in the assessment report or recap along with other data reports. This makes teacher performance appraisals ineffective. Based on the problems that occur, the author created a Teacher Performance Appraisal Information System to facilitate data collection, data search, assessment process, and report making. The research method carried out is a field study including observation and interviews, as well as conducting literature studies. From the results of the analysis, it can be seen that agencies need a new system to increase effectiveness and efficiency in the teacher performance appraisal process.